Algorithmic aspects of bipartite graphs - Mihály Bakonyi; Erik M. Varness (International Journal of Mathematics and Mathematical Sciences)
We generalize previous work done by Donald J. Rose and Robert E. Tarjan [2], who developed efficient algorithms for use on directed graphs. This paper considers an edge elimination process on bipartite graphs, presenting several theorems which lead to an algorithm for computing the minimal fill-in of a given ordered graph.